Hungarian Monitoring, 14 March 1988 . [Magyar rádiófigyelő], 1988. március 14 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev at talks in Belgrade - Shamir's visit to Washington - French-West German summit Domestic Affairs: - Károly Grósz meets leaders of 28 Hungarian churches - Hungarian-Romanian relations - March 15 commemorative events - MOKÉP Hungarian film body Külpolitika: - Gorbacsov Belgrádban tárgyal - Samír washingtoni látogatása - Francia-nyugatnémet csúcstalálkozó Belpolitika: - Grósz Károly magyarországi egyházak 28 vezetőjével találkozik - Magyar-román kapcsolatok - Március 15-ei megemlékezések - MOKÉP